Sensory Evaluation Of Purple Passion Fruit Jelly Candy (Passiflora Edulis f. Edulis Sims) - Rohman, Fikih Fathul; Putu Hemy Ekayani, Ida Ayu; Damiati, Damiati (Universitas Negeri Padang, 2025)
This study aims to determine the level of consumer acceptance of the innovation of purple passion fruit-based jelly candy products with a formulation of 120ml passion fruit juice, 120g granulated sugar and 35g gelatin. This study uses a quantitative descriptive analysis method, namely only looking for the average value through organoleptic (hedonic) testing. A total of 50 untrained panelists were involved to involved in assessing of color, aroma, taste, and texture attributes using a 5-point Likert scale. The results showed that this product received a positive response with the category